Importance of Apolipoprotein A-I in Multiple Sclerosis - Gardner, Lidia A.; Levin, Michael C. (Frontiers in Pharmacology, 2015)
Jean-Martin Charcot has first described multiple sclerosis (MS) as a disease of the central nervous system (CNS) over a century ago. MS remains incurable today, and treatment options are limited to disease modifying drugs. Over the years, significant advances in understanding disease pathology have been made in autoimmune and neurodegenerative components. Despite the fact that brain is the most lipid rich organ in human body, the importance of lipid metabolism has not been extensively studied in this disorder. In MS, the CNS is under attack by a person’s own immune system. Autoantigens and autoantibodies are known to cause devastation of myelin through up regulation of T-cells and cytokines, which penetrate through the blood brain barrier to cause inflammation and myelin destruction. The anti-inflammatory role of high-density lipoproteins (HDLs) has been implicated in a plethora of biological processes: vasodilation, immunity to infection, oxidation, inflammation, and apoptosis. However it is not known what role HDL plays in neurological function and myelin repair in MS. Understanding of lipid metabolism in the CNS and in the periphery might unveil new therapeutic targets and explain the partial success of some existing MS therapies.